The Effect of Special Teaching – Training Exercises For Developing Youth Long Jump Launch and Achievement - ِAbdulghani, Muhanned Yaseen; Dakhil, Ehab (Journal of Physical Education, 2017)
The importance of the research lies in the use of modern exercises that develop the athletes' achievements based on the leg's push strength and for the best angle of launch. The problem of the research lies in the weakness in performing launch and flight especially in youth athletes. The researcher used the descriptive method. The subjects were (5) youth long jumpers from the national center for gifted in athletics/ ministry of youth and sports. A pilot study was conducted followed by the main training program. The researchers used one group and applied long jump achievement test to identify the differences between pre and posttests. The data was collected and treated using proper statistical operations. The researchers concluded that the angle of launch plays an important role in developing achievement. Finally they recommended stressing that training should focus on launch angle